The Role of Parents in the Family to Increase Children's Learning Outcomes in Learning PJOK During the Pandemic Covid-19 - LUSIANA ROSYADI; AANG ROHYANA; AGUS ARIEF RAHMAT (Universitas Pendidikan Indonesia (UPI), 2022)
Introduction: Every child needs education because children's education can develop the interests and talents required. One effort to develop it is through a formal or non-formal institution. In these institutions learning activities are the most basic activities. Purpose: The purpose of the study was to determine the role of parents in the family in improving children's learning outcomes in PJOK learning during the Covid-19 Pandemic at SMPN 4 Tasikmalaya City. Methods: This study used a qualitative descriptive approach. This study's data collection techniques used triangulation techniques with observation, semi-structured interviews, and documentation. The sample used in the study was 20 parents of class VII students, and when the sample used the purposive sampling technique. Results: The results of the study show that the role of parents in improving children's learning plays an essential role in supporting the success of their children's education, especially during PJOK learning during the covid-19 pandemic; the part of parents is very much needed such as educating children to learn and accompanying children to learn, providing an atmosphere comfortable so that children focus on learning, encourage children to learn, provide the facilities needed for education, direct children according to the talents and interests of each child. Conclusions: parents play an essential role in supporting the success of their children's education, especially during PJOK learning during the covid-19 pandemic. The part of parents is very much needed such as educating children to learn and accompanying children to learn, providing a comfortable atmosphere so that children focus on learning, encouraging children to want to know, providing the facilities needed for education, direct children according to the talents and interests of each child.